2015
DOI: 10.1038/hr.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

Association between renal iron accumulation and renal interstitial fibrosis in a rat model of chronic kidney disease

Abstract: Iron accumulation is associated with the pathophysiology of chronic kidney disease (CKD). Renal fibrosis is a final common feature that contributes to the progression of CKD; however, little is known about the association between renal iron accumulation and renal interstitial fibrosis in CKD. Here we investigate the effects of iron chelation on renal interstitial fibrosis in a rat model of CKD. CKD was induced by 5/6 nephrectomy in Sprague-Dawley rats. At 8 weeks after operation, 5/6 nephrectomized rats were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…18,19 Although the results of our study demonstrated that a good correlation with histologic fibrosis scores was present. First, the contralateral kidney of rabbits (right kidney) was not studied because of rabbits' inherent anatomy, which includes a large stomach and many intestinal tubes around the right kidney leading to severe susceptibility artifacts, although several measurements were taken to reduce the artifacts.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…18,19 Although the results of our study demonstrated that a good correlation with histologic fibrosis scores was present. First, the contralateral kidney of rabbits (right kidney) was not studied because of rabbits' inherent anatomy, which includes a large stomach and many intestinal tubes around the right kidney leading to severe susceptibility artifacts, although several measurements were taken to reduce the artifacts.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, the renal perfusion and hypoxia play roles in renal fibrosis, which have been confirmed in previous studies. 18,19 Although the results of our study demonstrated that a good correlation with histologic fibrosis scores was present. The potential influences of these factors will be exploited in the future.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Consistent with the association between renal fibrosis and iron accumulation, several studies have shown that iron content is increased in fibrotic kidneys of the angiotensin II-infused rat, 32 Dahl salt-sensitive rat, 33 and 5/6 nephrectomized rat. 34 We, and others, have shown the antifibrotic effect of tissue iron reduction using iron chelators or iron restriction chow on the kidney. 15,33,34 Here, direct SFO treatment diminished renal EPO expression in the kidney with increased iron content.…”
Section: Discussionmentioning
confidence: 94%
“…34 We, and others, have shown the antifibrotic effect of tissue iron reduction using iron chelators or iron restriction chow on the kidney. 15,33,34 Here, direct SFO treatment diminished renal EPO expression in the kidney with increased iron content. Therefore, there is a close relationship between iron accumulation and renal fibrosis, resulting in the reduction of EPO expression.…”
Section: Discussionmentioning
confidence: 94%